The new needs friends: Simmelian strangers and the selection of novelty - Lampraki, Athanasia; Kolympiris, Christos; Grohsjean, Thorsten; Dahlander, Linus (Strategic Management Journal, 2024)
Abstract Research Summary The paradox of rejecting novel ideas while being motivated to select them exists in many realms. Deviating from prior research that investigated several internal levers to promote the funding of novel ideas in the sciences, we focus on an external lever by investigating how seconded employees increase the selection of novel ideas in two ways: (1) they select more novel ideas themselves, and (2) they influence permanent employees to do the same. Combining unique quantitative longitudinal data and 37 in‐depth interviews, we test our predictions in the secondment program at the National Science Foundation and find broad support for our theoretical arguments. Our findings have implications for scholars of science and innovation by proposing a relatively light‐touch intervention to facilitate the selection of novel ideas. Managerial Summary Organizations often face a paradox: they want to select novel ideas but tend to reject them. This study shifts focus from internal measures to an external solution, examining how seconded employees can help. Through both quantitative data and interviews at the National Science Foundation's secondment program, we found that seconded employees choose more novel ideas and influence permanent staff to do the same. This suggests a simple intervention can significantly boost the acceptance of innovative ideas, offering valuable insights for those in the science and innovation. Understanding this dynamic can empower managers to strategically leverage seconded employees, fostering a more innovative and adaptive organizational culture.